Acute myeloid leukaemia presenting with bilateral breast masses. (17th August 2018) - Cheng, Kai Chun Andrew; Li, Yan-Lin; Lam, Tina
Abstract : A 46-year-old woman with a known history of acute myeloid leukaemia presented with bilateral breast masses with pain and itchiness. The breast masses were hard on palpation. Mammogram was unremarkable. Ultrasound showed multiple conglomerated masses of heterogeneous hyperechogenicity and hypoechogenicity throughout all quadrants of bilateral breasts. Pathology showed mononuclear cells, suggestive of breast leukaemic infiltration. She was treated with decitabine and platelet transfusion.